High density of tryptase‐positive mast cells in human colorectal cancer: a poor prognostic factor related to protease‐activated receptor 2 expression. Issue 8 (29th August 2013) - Malfettone, Andrea; Silvestris, Nicola; Saponaro, Concetta; Ranieri, Girolamo; Russo, Antonio; Caruso, Stefano; Popescu, Ondina; Simone, Giovanni; Paradiso, Angelo; Mangia, Anita
Abstract Tryptase(+) mast cells (MCs), abundant in the invasive front of tumours, contribute to tissue remodelling. Indeed, protease‐activated receptor‐2 (PAR‐2) activation by MC‐tryptase is considered an oncogenic event in colorectal cancer (CRC). Recently, we have suggested NHERF1 as a potential new marker in CRC. In this study, we aimed to determine the distribution of tryptase(+) MCs and PAR‐2 and to examine the relationship between PAR‐2 and NHERF1, investigating their reputed usefulness as tumour markers. We studied a cohort of 115 CRC specimens including primary cancer (C) and adjacent normal mucosa (NM) by immunohistochemical double staining, analyzing the protein expression of MC‐tryptase, PAR‐2 and cytoplasmic NHERF1. MC density was higher in NM than in C. Tumours with high TNM stage and poor grade showed the highest MC density. A higher PAR‐2 immunoreactivity characterized tumours most infiltrated by MCs compared with samples with low MC density. Furthermore, PAR‐2 overexpression was associated with advanced TNM stage, poor grade and lymphovascular invasion (LVI). A positive correlation existed between tryptase(+) MC density and PAR‐2 expression. Cytoplasmic NHERF1 was higher in C than in NM and overexpressing tumours resulted associated with nodal and distant metastases, poor grade and LVI. PAR‐2 correlated with cytoplasmic NHERF1 and the PAR‐2(+)/cytoplasmic NHERF1(+) expression immunophenotype identified tumours associated with unfavourable prognosis and aggressive clinical parameters. Our data indicate that the high density of tryptase(+) MCs at invasive margins of tumours was associated with advanced stages of CRC and was strongly correlated with PAR‐2 expression.